2020
DOI: 10.1186/s12903-020-01181-9
|View full text |Cite
|
Sign up to set email alerts
|

Marginal and internal fit of full ceramic crowns milled using CADCAM systems on cadaver full arch scans

Abstract: Background: Chairside systems are becoming more popular for fabricating full-ceramic single restorations, but there is very little knowledge about the effect of the entire workflow process on restoration fit. Therefore, this study aimed to compare the absolute marginal discrepancy (AMD) and the full internal fit (FULL) of all-ceramic crowns made by two chairside systems, Planmeca FIT and CEREC, with detailed and standard mill settings. Methods: One upper molar was prepared for an all-ceramic crown in human cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…Many systems include chairside design software for prosthetic workflows. The first chairside CAD/CAM system was the CEREC; however, 3Shape and Planmeca systems also have their own design programs for chairside prosthetic workflows (e.g., inlays, onlays, crowns, short bridges) [ 59 , 72 , 73 ]. Our rating system is a uniform ranking scheme for all IOSs, but it is important to separately consider the findings of each assessment domain in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Many systems include chairside design software for prosthetic workflows. The first chairside CAD/CAM system was the CEREC; however, 3Shape and Planmeca systems also have their own design programs for chairside prosthetic workflows (e.g., inlays, onlays, crowns, short bridges) [ 59 , 72 , 73 ]. Our rating system is a uniform ranking scheme for all IOSs, but it is important to separately consider the findings of each assessment domain in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The same is reported by Persson,Yang,Miura,Souza,and Ortorpa et al [1,[22][23][24][25][26]. In the CAD/CAM restorations, the precision of the data acquisition system, the capability to combine and match images, the designing software, the milling machine, and the machine's bur size must be added to the list [10,27,28]. The size of the milling bur is important because the width of the intaglio surface could not be smaller than the smallest bur of the milling machine [29,30].…”
Section: Discussionmentioning
confidence: 90%
“…When comparing the results of this study with the published articles on the accuracy of conventional and digital impressions, it was found that our study was consistent with a study conducted by János Vág et al on the upper jaw of a full-tooth human cadaver which found that conventional impressions were more accurate than digital impressions. Despite the different intraoral scanning systems used [ 26 ]. Our results correspond to Ender's study, as it found that the deviation mean of the conventional impressions of (53 ± 2 μm) was significantly different from that of the Trios 3 (μ8 ± 156) and CS 3600 (29 ± 365) intraoral scanners; however, it was significantly lower than the values ​​for element 1 (531 ± 26), element 2 (246 ± 11), emerald (317 ± 13), Omnicam (174 ± 11), and Planscan (903 ± 49) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%